Pemanfaatan Media Sosial Sebagai Strategi Inovatif Dalam Pendidikan Islam di Era Digital - Mawaddah Rahmah, Noor; Shofiyati, Nur; Sucia Dewi, Endah; Hidayati, Noorazmah (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
The rapid growth of information technology, particularly social media, has transformed various aspects of life, including Islamic education. Platforms such as Instagram, YouTube, WhatsApp, and TikTok provide new opportunities to deliver Islamic teachings creatively and contextually, especially to younger audiences. This study aims to analyze the potential of social media in supporting Islamic education and to identify the challenges it presents. The research employed a library-based method by reviewing books, scholarly articles, and relevant previous studies, followed by a qualitative analysis to synthesize findings. The results indicate that social media offers several benefits: expanding the reach of Islamic educational institutions, introducing innovative learning strategies, reinforcing religious values, and enabling flexible preaching activities. However, it also raises concerns such as moral decline, cyberbullying, reduced concentration, lower interest in learning, negative behavioral patterns, and excessive dependence on technology. Despite these challenges, social media can enhance Islamic education by widening access to resources, fostering collaboration, increasing motivation, and promoting learner autonomy. In conclusion, social media has significant potential to strengthen Islamic education if utilized wisely. The active involvement of teachers, parents, and institutions is essential to ensure its alignment with Islamic values and its positive contribution to students’ character development.